The Child - and Youth Picture of the Registered Professional Journals of Hungarian Nursery School History from the XIX Century to Present Days (Training and Practice : Journal of Educational Sciences, 2012)
The present paper summaflzes the approach of the 183 years old Hungarian child-picture of nursery school history regarding the professional journals. The paper is a multidisciplinary summary beginning at the publishing of the first ’Közlemények a kisdedóvás és gyermeknevelés köréből’ (published in 1843, Buda, the journal does not have any continuation) and finishing at the professional journal called ’Óvodai Nevelés’, where we can meet writings about the child concept of the 21st century. This paper represents those social, political periods which, based on ideologies, formed the theories and aspects of childcare in pedagogy.